Longitudinal trends in the frequency of medium and fast race winning times in Australian harness racing: Relationships with rules moderating whip use. - Bethany Wilson; Bidda Jones; Paul McGreevy (PLoS ONE, 2018)
The use of whips in racing is subject to current debate, not least because the prospect that fatigued horses cannot respond renders the practice futile and inhumane. The racing industries maintain whip use is a form of encouragement and that the rules of racing that govern whip use safeguard horse welfare. The current study examined longitudinal trends in the frequency of medium and fast race winning times in Australian harness racing between September 2007 and August 2016 to explore relationships with a series of changes that moderated whip use. The first change, introduced January 2010, moderated whip action so that horses were struck with less force. Subsequent amendments reversed this change for the final 200m of the race except in one racing jurisdiction. However, those amendments were eventually reversed, restoring the first rule change in all geographic locations. Despite whip use being regulated from January 2010, a long-term trend of increased frequency of both fast and medium winning times over 1609m (~1 mile) was noted. Even after adjusting for this trend, all whip handling codes were associated with greater odds of winning times being less than 1:55 minutes compared with the pre-2010 period. A similar finding for times less than 2:00 minutes did not reach statistical significance. Additionally, the periods immediately before and after introducing the most stringent regulations were compared. This revealed that, when introduced in 2010, these regulations were associated with faster winning times. Their re-introduction in 2016, was associated with no significant differences. Despite concerns that tightening of whip regulations might reduce performance, none of our analyses revealed any significant reduction in either fast or medium winning times in races following the tightening of regulations governing the use of the whip. These findings question the putative need for whips to improve racing performance.